2014
DOI: 10.3389/fncir.2014.00071
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic dynamics contribute to long-term single neuron response fluctuations

Abstract: Firing rate variability at the single neuron level is characterized by long-memory processes and complex statistics over a wide range of time scales (from milliseconds up to several hours). Here, we focus on the contribution of non-stationary efficacy of the ensemble of synapses–activated in response to a given stimulus–on single neuron response variability. We present and validate a method tailored for controlled and specific long-term activation of a single cortical neuron in vitro via synaptic or antidromic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 54 publications
1
27
0
Order By: Relevance
“…6D) activity. Other groups have also reported that blocking AMPA receptors is enough to abolish this activity (Bonzano et al 2006;Reinartz et al 2014). Furthermore, in a network that is driven uniquely by AMPA receptors, we did find maximal spike rates (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…6D) activity. Other groups have also reported that blocking AMPA receptors is enough to abolish this activity (Bonzano et al 2006;Reinartz et al 2014). Furthermore, in a network that is driven uniquely by AMPA receptors, we did find maximal spike rates (Fig.…”
Section: Discussionsupporting
confidence: 62%
“…Electrophysiology and MEA recordings. Primary cortical cultures were obtained from postnatal Wistar rats, employing standard methods 34 . Briefly, after mechanical and enzymatic dissociation of the cerebral cortices of postnatal day 0 (P0) pups, cells were plated at a final density of ,1.500 mm 22 on glass coverslips and of 6.500 mm 22 on commercial microelectrode arrays (MEAs; Multichannel Systems GmBH, Reutlingen, Germany).…”
Section: Research Lettermentioning
confidence: 99%
“…In vitro, we used a single stimulation electrode to directly (nonsynaptically) activate multiple neurons (Marom and Shahaf 2002;Wagenaar et al 2004;Reinartz et al 2014), and in simulations, we directly activated a set of neurons, which was usually sufficient to trigger a network burst. Stimuli were applied either as low-frequency pulses or as tetani.…”
Section: Discussionmentioning
confidence: 99%